Synthesis and optimization of silver nanoparticles-antibody Herceptin conjugation for surface-enhanced Raman scattering (SERS) - Nasser Jaafer Zahid; Bejan Hashime; Mohamed Jafad Rasib; Afshin Mohtfir (Engineering and Technology Journal, 2015)
We have developed surface-enhanced Raman spectroscopysubstratecomposed of antibody-conjugated silver nanoparticles as a functional nanoprobe. In this study, we synthesized silver nanoparticles with the pMBA linker for binding to antibody Herceptin and analyzed the binding of Herceptin to silver nanoparticles by Fourier Tranform Infrared (FT-IR). Our results clearly showed that a spherical shape of silver nanoparticles with a diameter of 50 µm has been performed. Furthermore, the obtained SERS probe apparently indicated that the intensity of antibody-conjugated silver nanoparticles as a SERS sensitive probe is increased by an enhancement factor of 105.